Distribution of lead and zinc in soil over the Bitola region, Republic of Macedonia - Dimovska, Bojana; Stafilov, Trajče; Šajn, Robert; Bačeva, Katerina (Geologica Macedonica, 2014)
Data for the distribution of lead and zinc in topsoil and subsoil over the Bitola region, Republic of Macedonia, known for its coal mine and thermoelectric power plant are presented. The study area (1400 km2) is covered by a sampling grid of 5×5 km with a total of 58 spots. The samples were collected at two depths: topsoil (0–5 cm) and subsoil (20–30 cm). The samples were analyzed by inductively coupled plasma-atomic emission spectrometry (ICP-AES). The obtained results of these two elements were statistically processed and maps of areal distribution were prepared. It was assumed that the higher contents of Pb and Zn are connected with the anthropogenic influence by the fly ash from the thermoelectric power plant deposed on the open as well as the influence of the high frequency traffic near the city of Bitola. Key words soil; lead; zinc; Bitola; Republic of Macedonia